STUDI AL-QURAN TENTANG PERJANJIAN PERDAGANGAN LINTAS BATAS PEMERINTAH INDONESIA-MALAYSIA - Muzalifah Muzalifah (IAIN Padangsidimpuan, 2018)
Cross-border trade agreement between Indonesia-Malaysia Government discuss about trading for the people residing in state borders area. However along with the times these agreements become less effectively. The mentioned because the agreement was long time ago and abuse of rigts by certain peoples. Thereby, the agreement needs reexamination because it is less relevant to the Indonesia economic development nowadays. It can also be detrimental to one of the parties in the state borders area. It is not contary to the tenetof islam as concept of fiqh rules on the basis of the society benefits that is part of a study of Al-Qur’an.